A Dissident Liberal the political writings of Peter Baume - Baume, Peter (ANU Press, 2015)
In the 'broad church' of the Australian Liberal Party, rarely has there been a maverick so unrelenting in his commitment to personal principles as Senator Peter Baume. Over a parliamentary career spanning 17 years, three ministerial portfolios and five party leaders, Baume was increasingly pitted against his own party room. In A Dissident Liberal: The Political Writings of Peter Baume, we learn of personal threats, crises, constitutional confrontation and the tension between conservatism and classical liberalism-and between ideology and toeing the party line. This collection of personal observations, speeches and commentaries on contentious policy issues presents a valuable resource for students of Australian political history.